Kajian Tingkat Kebisingan Di kawasan Bandara Pinang Kampai Kota Dumai - Adillah, Muhammad Iqbal; Sasmita, Aryo; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pinang Kampai Airport Dumai City serves domestic flights, and home base for BNP-B (National Board for Disaster Management) helicopters. The noise level is influenced by the flight activity when monitoring the area of Dumai City Fire Area around it. The purpose of this study was to determine the noise intensity at the airport and surrounding residential areas, the duration of noise exposure, and the mapping of the noise dispersal pattern. Noise measurement method based on KepMenLH No 48/1996, and the device in use is Sound Level Meter (SLM). Measurement of sound pressure level (Leq) lasts for two days on weekdays and holidays. Based on the results of data processing of 8 measurement points conducted on weekdays and holidays, the results show the highest noise level is on the southern runway area on the working day of 100.8 dB and on the holiday of 101.0 dB (exceeding the standard quality of 85 dB, Kepmenaker No. 51/1999) and the highest noise level in the residential area around the airport on weekdays are in the eastern settlement of 82.41 dB and on holidays of 86.59 dB which overall exceeds the 55 dB determined standard, KepMenLH No. 48/1996). Noise control can be done by making noise barrier and using noise-absorbing materials on building construction. Keywords: Noise, airport, PinangKampaiAirport